Eliminating Qanun Jinayat in Resolving Sexual Violence in Indonesia: A Comparative Study of the TPKS Law and Qonun Jinayat - Nur Anisah, Laili; Wibisono, Anditya Ariesta (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2024)
Law Number 12 of 2022 concerning Crimes of Sexual Violence (UU TPKS) was passed in April 2022 after waiting almost 12 years when it was submitted as an initial draft law to the DPR. Unlike other laws, TPKS Law was designed using a bottom-up system to address the problem of overcoming sexual violence in Indonesia, the number of which increases every year. However, not all regions in Indonesia will use the TPKS Law when cases of sexual violence occur. Aceh Province is the only province that, based on special autonomy, is allowed to have its criminal law called Qanun Jinayat. This research compares the regulations regarding preventing sexual violence contained in TPKS Law and the Aceh Qanun Jinayat. It looks at the threat to the protection of victims of criminal acts, especially victims of criminal acts of sexual violence. This research is normative legal research, which analyzes statutory regulations. The results of the study show that TPKS Law regulates the prevention of sexual violence more comprehensively than the Qanun Jinayat, which requires more comprehensive protection for victims than the Qanun Jinayat. There are also articles in the Qanun Jinayat that tend to cause revictimization, rather than protecting victims.